Individual and community-level determinants of cervical cancer screening in Zimbabwe: a multi-level analyses of a nationwide survey - Isabirye, Alone; Elwange, Bob Charlestine; Singh, Kavita; De Allegri, Manuela (BMC women's health, 2022)
Despite the benefits of cervical cancer (CC) screening to reduce the disease burden, uptake remains limited in developing countries. This study aims to assess the individual and community-level determinants of cervical cancer screening among women of reproductive age in Zimbabwe.
Gesehen am 09.11.2022